Crystallization and preliminary crystallographic analysis of d-alanine-d-alanine ligase from Streptococcus mutans - Lu, Yong-Zhi (International Union of Crystallography, 2007)

(untitled)
d-Alanine-d-alanine ligase is encoded by the gene ddl (SMU_599) in Streptococcus mutans. This ligase plays a very important role in cell-wall biosynthesis and may be a potential target for drug design. To study the structure and function of this ligase, the gene ddl was amplified from S. mutans genomic DNA and cloned into the expression vector pET28a. The protein was expressed in soluble form in Escherichia coli strain BL21 (DE3). Homogeneous protein was obtained using a two-step procedure consisting of Ni(2+)-chelating and size-exclusion chromatography. Purified protein was crystallized and the cube-shaped crystal diffracted to 2.4 Å. The crystal belongs to space group P3(1)21 or P3(2)21, with unit-cell parameters a = b = 79.50, c = 108.97 Å. There is one molecule per asymmetric unit.